On the problem of protection of the members of agricultural enterprises with the participation of deliberative service - Тараненко, Людмила Станіславівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The practice of deciding the cases by courts as to the property shares and land shares are revised in thearticle. The court decisions on these problems with the participation of agricultural enterprises of cooperative type are analyzed. The problems of hearing the share cases by the courts are open. The characteristic of thelegislature, which regulate the problem of shares is given. Separate conditions of legal services agreement on defending the rights of agricultural enterprises by deliberative service are explained. The role of executiveservice on the execution of court decisions with the participation of deliberative service is open.